Positional cerebral ischaemia. Issue 4 (April 1976) - Caplan, L R; Sergay, S
Abstract : Four patients are described in whom recurrent, dramatic transient clinical worsening accompanied elevation from the supine toward the sitting position, though postural hypotension was not present. In each patient occlusive cerebrovascular disease was documented angiographically. During an acute stroke syndrome, some patients' compensatory capacity may be so tenuous that postural changes may produce clinical worsening. Possible mechanisms are discussed.